Developing the Leadership Capacity of Community Leaders in Local Development Planning in the Mae Sai Special Economic Zone, Chiang Rai Province - Intanon, Sirimas; Kaewsri, Phuripat; Imiwat, Prayoon (Journal of Public Administration Chiang Rai Rajabhat University, 2026)
This research study has the objective 1) To study the problems and obstacles of community leaders in preparing local development plans in the Mae Sai Special Economic Zone area. Chiang Rai Province. 2) To analyze the potential of community leaders in preparing local development plans in the Mae Sai Special Economic Zone area. Chiang Rai Province. and 3) to propose guidelines for developing the potential of community leaders in preparing local development plans in the Mae Sai Special Economic Zone area. Chiang Rai Province The study employed quantitative research methods, with a population sample consisting of 36 community leaders and officials involved in local development planning, and 375 local residents from Pong Ngam Subdistrict. Data were collected using questionnaires and analyzed through frequency, percentage, mean, and standard deviation. In addition, qualitative research was conducted with 10 key informants, and data were analyzed using content analysis. The results of the study of problems and obstacles found that community leaders have problems and obstacles in preparing local development plans. The budget aspect is at the highest level, followed by legal regulations, and public participation. The results of the analysis of the potential of community leaders found that community leaders have high potential in every aspect, and guidelines for developing the potential of community leaders in preparing local development plans in the Mae Sai Special Economic Zone area. Chiang Rai Province, 4 areas: 1) the process of making a local development plan 2) Management aspect 3) Quality of life of the people 4) Participation in the preparation of local development plans.